PENERAPAN MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE BERBANTUAN MEDIA TEKA TEKI SILANG UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Ranti Rahmawati Nurhalizah; Ai Nur Solihat; Kurniawan Kurniawan (JOURNAL SAINS STUDENT RESEARCH, 2025)
The purpose of this study to determine the effectiveness of the Think Pair Share type of cooperative learning model assisted by crossword puzzle media in improving the learning outcomes of tenth-grade students in economics subjects. The research used a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 44 students, with 21 in the experimental class and 23 in the control class. The results showed a significant improvement in the experimental class with an average N-Gain of 0.84 and a posttest score of 91.47. The significance value (2-tailed) was 0.020 < 0.05, indicating that the model is effective in enhancing student learning outcomes.